Investor Sentiment Toward Puma Stock Performance During the #Boycottpuma Campaign: A Case Study From Börsennews - Lestari, Novri Ayu; Indraswari, Citra Rahayu (Contemporary Studies in Economic, Finance and Banking, 2025)
Political and ethical boycott movements increasingly influence investor sentiment in global financial markets. The #BoycottPuma campaign, targeting Puma’s ties to Israeli institutions, is a key example. This study aims to examine the impact of the campaign on investor sentiment toward Puma’s stock by analyzing user discussions on Börsennews using sentiment analysis and NLP techniques. Findings reveal that despite Puma’s stable financials, negative sentiment dominated due to reputational concerns.